HUBUNGAN FAKTOR INDIVIDU DENGAN PERASAAN KELELAHAN KERJA DAN WAKTU REAKSI PENGEMUDI MOBIL TANGKI DI PT. X TAHUN 2011 - , meilya farika indah ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this research is to determine the relationship among individual factors with feeling of occupational fatigue, and reaction time of fuel truck drivers in PT X. This study is a descriptive analytical research using Cross Sectional design. The research subject is fuel truck drivers in PT X, with sample consisting of 57 persons. Research data are analyzed by using correlation test of Pearson Product Moment and Multiple Linear Regression. The result of the research shows that relationship exists between individual factors (age, working period and work duration) with feeling of occupational fatigue, in which work duration is the most dominant factor with 20.357% contribution. There is a significant relationship between individual factors (age, working period and work duration) with reaction time, in which work duration is the most dominant variable contributing to reaction time of fuel truck drivers in PT X, with 23.780% contribution. This research also shows significant relationship between feeling of occupational fatigue with reaction time. It is shown by the fact that fatigue gives positive contribution to reaction time of fuel truck drivers in PT X, with 30.5% contribution. Keywords: individual factors